ISLAMIC LAW AND SCIENCE IN NU-MUHAMMADIYAH'S LUNAR CALENDAR DETERMINATION - Musonnif, Ahmad (Al-Hilal: Journal of Islamic Astronomy, 2024)
This article examines the paradigm shift in determining the start of the Islamic month, driven by advancements in science and technology. Initially, Muslims relied on moon sighting (rukyat al-hilāl), but the mastery of mathematics and astronomy led some to adopt calculations (ḥisāb). The study focuses on the differing approaches of the Nahdlatul Ulama (NU) Baḥṣul Masāil and the Muhammadiyah Tarjih forum. With the advent of computers and the internet, Muhammadiyah embraced ḥisāb and the global Islamic calendar. Meanwhile, NU integrates traditional rukyat with modern tools like mathematics, computers, and photographic technology while maintaining a regional calendar. These differences highlight Muhammadiyah’s modernist paradigm and NU’s eclectic approach, blending tradition with modernity.